Strategic vision of directions of spatial development of industrial cities in the post-war years - К. М. Tkachenko (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2023)
The article stated that Russia’s military aggression against Ukraine caused and continues to cause enormous damage to industrial cities, as a result of which: control over the occupied territories was lost, production facilities were physically destroyed as a result of terrorist missile attacks, houses, infrastructure objects, etc. were destroyed. The plans of Ukrainian industrial cities regarding their spatial development, modernization, improvement of the quality of life and green transformation were also destroyed. It is emphasized that Davis and Weinstein (2002) on the example of Japan, Germany, South Korea, etc. countries emphasize that with proper financing, damaged industrial cities can recover quite quickly. It has been proven that in this situation the main thing is to correctly predict the future of their spatial development, to form its strategic vision and to clearly define the priority vectors of reconstruction. It is justified that at the regional level it is necessary: to develop clear plans for the reconstruction of industrial cities on the basis of sustainable development, i.e., in addition to the targeted economic and social indicators of the recovery and spatial development of cities, such plans must contain a mandatory ecological component with an analysis of the current situation, a list of mechanisms ( plans) solving existing environmental problems and preventing their occurrence in the future; create a map of industrial cities, where the territory of each, based on an understanding of the real possibilities for the return of the population that left these territories, should be described in detail in order to make an optimal decision regarding reconstruction or further spatial development; it is extremely important to ensure the comprehensive nature of the reconstruction; create reliable information and sufficiently reliable forecasts regarding internal and external threats and opportunities; to demonstrate in advance that industrial cities are able to properly manage funds for recovery. The priority vectors of the spatial development of industrial cities on medium and long-term time horizons have been determined. It is emphasized that their introduction in the post-war years will provide a double benefit - it will form the trust of donors, ensure the reconstruction of industrial cities and the progress of their further spatial development.